Saskatchewan : South sheet - Canada. Department of Mines and Technical Surveys (Department of Mines and Technical Surveys Canada, 1963)
This is a general map of Saskatchewan in 1963 showing highways and roads (paved and graveled); gas and oil fields, mines and pipelines; First Nations reserves; national and provincial parks; railways, cities and towns. It consists of 2 parts - North sheet and South sheet (see also Saskatchewan : North sheet). "M.C.R. 45 (Sheet 1)" Scale 1:760,320, or 12 miles to 1 inch. Relief shown by spot heights. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Shows highways and roads (paved and graveled); gas and oil fields, mines and pipelines; First Nations reserves; national and provincial parks; railways, cities and towns.